In vitro Assays of Inorganic Arsenic Methylation - Drobna, Zuzana (2009)
Inorganic arsenic is extensively metabolized to produce mono-, di-, and trimethylated products. The formation of these metabolites produces a variety of intermediates that differ from inorganic arsenic in terms of patterns of distribution and retention and in toxic effects. In order to elucidate the pathway for arsenic methylation, it was necessary to develop a reliable in vitro assay system in which the formation of methylated metabolites could be monitored. Here, in vitro assay system that uses the postmicrosomal supernate from rat liver is used as the source of the enzymatic activity that catalyzes methylation reactions. This system can be used to study the requirements for methylation reactions (e.g., identifying the donor of methyl groups) and for screening of compounds as potential activators or inhibitors of arsenic methylation.